Making the mundane remarkable: an ethnography of the 'dignity encounter' in community district nursing. Issue 4 (8th April 2023) - Stevens, Emma; Price, Elizabeth; Walker, Elizabeth
Abstract: The concept of dignity is core to community district nursing practice, yet it is profoundly complex with multiple meanings and interpretations. Dignity does not exist absolutely, but, rather, becomes socially (de)constructed through and within social interactions between nurses and older adult patients in relational aspects of care. It is a concept, however, which has, to date, received little attention in the context of the community nursing care of older adults. Previous research into dignity in health care has often focused on care within institutional environments, very little, however, explores the variety of ways in which dignity is operationalised in community settings where district nursing care is conducted 'behind closed doors', largely free from the external gaze. This means dignity (or the lack of it) may go unobserved in community settings. Drawing on observational and interview data, this paper highlights the significance of dignity for older adults receiving nursing care in their own homes. We will demonstrate, in particular, how dignity manifests within the relational aspects of district nursing care delivery and how tasks involving bodywork can be critical to the ways in which dignity is both promoted and undermined. We will further highlight how micro-articulations in caring relationships fundamentally shape the 'dignity encounter' through a consideration of the routine and, arguably, mundane aspects of community district nursing care in the home.